Environmental justice: An exploratory snapshot through the lens of Canada's mainstream news media. (27th October 2015) - Deacon, Leith; Baxter, Jamie; Buzzelli, Michael
Key Messages: Disjunctures occur between what is covered by the Canadian news media and empirical studies of environmental threats to communities. Canadian newspapers overtly ignore and subtly downplay through discourse environmental threats to marginalized local communities faced with pollution. A wide array of avenues for future research are suggested to contrast different forms of news media and compare the scale of both coverage and discourse. Abstract : This exploratory analysis opens up new avenues for research in the area of media analysis and environmental justice by combining quantitative content analysis with qualitative discourse analysis of 15 Canadian mainstream newspapers to explore how Canadian print news media act not only as a filter but also as a constructor or silencer of environmental justice discourses. Disjunctures occur between what is covered by the Canadian news media and what local studies of place and injustice suggest are the on‐the‐ground realities. In particular, disadvantaged communities who have experienced or are experiencing significant environmental exposures are consistently underrepresented in key mainstream Canadian news media coverage. Consequences of this underrepresentation suggest indifference and may serve to perpetuate existing cases of environmental inequity. We suggest this muting happens not only through lack of reporting but also through discourse in existing reporting. This exploratory study suggests the need for ongoing research to examine: 1) how pervasive these phenomena are in various Canadian news media outlets, 2) how they manifest and with what impacts at the local scale in particular places, and 3) the overall impact of environmental justice as a discourse of resistance on the ground versus in the minds of academics.